2019
DOI: 10.1108/jfp-07-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

“Give it a Try”: experiences of black, Asian and minority ethnic young men in a prison-based offender personality disorder service

Abstract: Purpose Within the current offender personality disorder (OPD) pathway in the UK, black, Asian and minority ethnic (BAME) populations are underrepresented. Fewer BAME offenders are engaging with services despite being proportionately identified for inclusion and referred on to the pathway. The paper aims to discuss this issue. Design/methodology/approach This qualitative study explored the experiences of 11 BAME men engaged in a prison-based OPD service for young offenders to identify the highlights and chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The prevalence of personality disorder for white British, black/mixed and Asian/mixed populations is displayed in Table 3. Of the 10 included studies, nine studies reported prevalence data (Crawford et al, 2012;Garrett et al, 2011;Geraghty and Warren, 2003;Hossain et al, 2018;Hunter et al, 2019;Leese et al, 2006;McKenzie et al, 2019;Pereira et al, 2005 andRaffi andMalik, 2010). Five studies presented ethnicity data separately from personality disorder data (Crawford et al, 2012;McKenzie et al, 2019;Pereira et al, 2005;Leese et al, 2006;Hossain et al, 2018) and three studies comprised of samples where all participants were diagnosed with a personality disorder (Garrett et al, 2011;Geraghty and Warren, 2003;Raffi and Malik, 2010).…”
Section: Collating Summarising and Reporting The Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of personality disorder for white British, black/mixed and Asian/mixed populations is displayed in Table 3. Of the 10 included studies, nine studies reported prevalence data (Crawford et al, 2012;Garrett et al, 2011;Geraghty and Warren, 2003;Hossain et al, 2018;Hunter et al, 2019;Leese et al, 2006;McKenzie et al, 2019;Pereira et al, 2005 andRaffi andMalik, 2010). Five studies presented ethnicity data separately from personality disorder data (Crawford et al, 2012;McKenzie et al, 2019;Pereira et al, 2005;Leese et al, 2006;Hossain et al, 2018) and three studies comprised of samples where all participants were diagnosed with a personality disorder (Garrett et al, 2011;Geraghty and Warren, 2003;Raffi and Malik, 2010).…”
Section: Collating Summarising and Reporting The Resultsmentioning
confidence: 99%
“…Ethnically racialised prisoners were also significantly less likely than white prisoners to have problems associated with personality disorder. Hunter, Craig and Shaw (2019) focus on an OPD pathway service in Aylsebury, England. Within this study they make reference to prevelance and draw comparisons with personality disorder in prison populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations